Corona Virus Disease (COVID-19) and Other External Factors as Determinants of Accommodation and Restaurant Services in Kenya - Evans Ovamba Kiganda; Margaret Atieno Omondi (Archives of Current Research International, 2020)
Aim: The aim of this study is to investigate the influence of corona virus disease and other external factors on growth of accommodation and restaurant services (ARS) in Kenya. Study Design: The study employed quantitative research design involving quarterly time series data from quarter 1 of 2014 to quarter 1 of 2020. The data set was obtained from Kenya National Bureau of Statistics (KNBS). Methodology: The study employed unrestricted vector autoregression to investigate the changes in the growth of accommodation and restaurant services. Results: Results indicated that COVID-19, professional, administrative and support services, construction and past ARS growth at 1 to 3 lags influences growth of ARS in Kenya negatively. On the other hand, real estate growth, time trend, tax on products, other services, education, manufacturing, information and communication and past growth in ARS at lag 4 influences growth in ARS sector positively. It was also noted that growth in agriculture and transport and storage do not influence growth of ARS in Kenya. Conclusion: In conclusion, COVID-19, professional, administrative and support services, construction and past ARS growth, real estate growth, time trend, tax on products, other services, education, manufacturing, information and communication are the main determinants for the growth of ARS in Kenya.